An industrial quality control study on Eurotiles Industrial Corporation - Derit, Lea; Martinez, Deanne Ambata; Parino, Maria Karren Torrano (Diliman, Quezon City College of Engineering, 2003)
Eurotiles Industrial Corporation is a manufacturer of superior ceramic tiles that carry the trade name Eurotiles located in Emilio Aguinaldo Highway Biga, Silang, Cavite. The company under study produces mainly tiles with sizes of 8?x8?, 12?x12? and 16?x16. The 12? x 12? tiles constitute 70% of the total monthly production of the company. The company?s expected total monthly production is 6,251,478 tiles and 70% of this tiles is 12? x 12? in size. In relation to this, the group focused the quality study in the 12? x 12? ceramic tile. There are several processes involved in tile manufacturing. These are the weighing, ball-milling, agitating, spray drying, body pressing, body drying, glazing and firing operations. Three problems were identified using Pareto Analysis with the data on six months, (from January to June 2002). These are the cracks generated after the firing process, unevenness of glaze coating and variation in tensile strength of the 12? x12? ceramic tile. Using Cause and Effect Analysis, the group determined several factors affecting the problem. For cracks, the root cause was determined to be prolonged exposure to the kiln, as well as variability in temperature and pressure. As for the unevenness of the glaze coating, the clogging of the glaze sprayer was identified to be the root cause. Lastly, the variability of the quality of the raw materials was identified as the cause of the variation in the tensile strength of the green ware tile. Doing a Failure Mode Effect and Criticality Analysis, the resulting priority operations are the body drying with an RPN of 140, glazing with RPN of 126 and the firing process with an RPN of 168, which are the processes involved in the problem analysis. Statistical Process Control (SPC) Charting and Process Capability Analysis were conducted using a six-month data, beginning on January 2002 to June of 2002, in order to know if the processes are capable of meeting the required quality of tiles. The results showed that the three processes involved are all capable of meeting the specific requirements set by the company. The cost of quality was also computed in order to know the contributions of rework caused by the problems identified. The total cost of quality is Php 9,301.80. Finally, the group recommended that stricter machine maintenance scheduling and keen monitoring of temperature and pressure setting all throughout the production processes be done to minimize, or if possible, avoid any variations of these factors from the set standards. Also, a consistent formulation and consistent preparation of the glaze material must be established in order to address the unevenness of the glaze coating problem. A design of experiment was recommended to be conducted in the glaze coating process in order to know if clogging of the glaze sprayer is experienced with different glazes.
Submitted in partial fulfillment of the course requirements in IE 135 : Industrial Quality Control
Keywords: Eurotiles Industrial Corporation; Textiles industry; Quality control